Silicon quantum dot sensors for an explosive taggant, 2, 3-dimethyl-2, 3-dinitrobutane (DMNB). Issue 53 (18th May 2016) - Kim, Jin Soo; Cho, Bomin; Cho, Soo Gyeong; Sohn, Honglae
Abstract : Conduction band edge dependent photoluminescence (PL) quenching by electron transfer was observed. PL from silicon quantum dots (Si QDs) was quenched by 2, 3-dimethyl-2, 3-dinitrobutane (DMNB), however PL from cadmium selenide (CdSe QDs) was not quenched by DMNB. Abstract : Silicon quantum dots obtained by the reaction of magnesium silicide with ethylenediamine dihydrochloride were utilized to investigate the sensing mechanism and sensitivity for DMNB detection applications. Sensing DMNB provided us with evidence that Si QDs with a higher lying conduction band have better sensitivity compared to CdSe QDs.